2000
DOI: 10.1056/nejm200004063421403
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Balloon Angioplasty on Hypertension in Atherosclerotic Renal-Artery Stenosis

Abstract: In the treatment of patients with hypertension and renal-artery stenosis, angioplasty has little advantage over antihypertensive-drug therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
445
1
34

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 816 publications
(500 citation statements)
references
References 23 publications
11
445
1
34
Order By: Relevance
“…Identification of renal artery stenosis still seems useful since surgical or percutaneous treatment of these lesions may improve blood pressure control and/or stabilise renal function, even though the latter has been disputed in a recent publication. 14 Numerous diagnostic tests have been proposed to identify patients with renovascular disease. However, none of them has received widespread clinical acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of renal artery stenosis still seems useful since surgical or percutaneous treatment of these lesions may improve blood pressure control and/or stabilise renal function, even though the latter has been disputed in a recent publication. 14 Numerous diagnostic tests have been proposed to identify patients with renovascular disease. However, none of them has received widespread clinical acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…7 Besides treatment with medication, patients with hypertension and renal artery stenosis can be treated by percutaneous transluminal renal angioplasty, which may lead to improvement or even cure of hypertension. 8 In our trial on diagnosis and treatment of patients with hypertension and renal artery stenosis, we found that the patients who were treated with angioplasty needed less antihypertensive drugs to control blood pressure than the patients who were treated with medication only 9 ( Table 1). Since it has been demonstrated that patients who use less antihypertensive medication report a better health status, 10 the patients in our trial who received angioplasty may have experienced an improvement in their quality of life compared to the patients who received medication only.…”
Section: Introductionmentioning
confidence: 91%
“…The patients were randomly allocated to balloon angioplasty (n ¼ 56) or to increased antihypertensive drug therapy (n ¼ 50). 9 The primary outcome of the trial was diastolic blood pressure. Quality of life was measured as a secondary outcome measure.…”
Section: Patientsmentioning
confidence: 99%
“…Only three such trials have been published so far and all were quite small. [4][5][6] Of the patients randomised to PCTA, only a tiny minority underwent stent insertion. In general the improvement in blood Table 1 Question (with regard to angioplasty and stenting) Answer…”
mentioning
confidence: 99%